Identification On Mineralogical And Mechanical Properties Of Rock - Saril, Muhammad Amin (Universiti Sains Malaysia, 2022)
Mechanical properties of rock depend on the mineralogical properties. Mechanical properties of the rocks categorized as one of important criteria to rocks characteristics and important in industry such as construction, mining and Quarry. This study is conducted throughout the observation of thin section with mechanical test in the laboratory which are Schmidt Hammer, Ultrasonic velocity P-wave, Unconfined Compressive Strength Test, Brazilian Tensile Strength Test and Point load. There are nine sample are preparing for thin section which are foliated shale, Siltstone, Sandstone, Coarse-Grain Sedimentary rock, Quartzite and four different type of limestone while seven sample undergoes mechanical test which are foliated shale, siltstone, sandstone, coarse-grain sedimentary rock, quartzite, and sample of granite rock from different area. Mechanical test is conducting by preparing the sample into the suitable size and shape according to American Society for Testing and Materials (ASTM) standard. The mechanical test conducted resulting the stress value with graph of load and displacement. The thin section sample is observed under microscope. Grain and mineral composition are analysed when observed through microscope and can correlate with the mechanical properties such as the existence of quartz in mineral composition of the rock. The result of mechanical test is correlated among themselves to identify the significant of rock strength through different mechanical test. Moreover, the mechanical test on rock is correlate with the mineral identification from observation through thin section to classify the rock as hard rock or weak rock.